Pengetahuan dan Sikap Masyarakat terhadap Vaksinasi COVID19 - Maimuna Latuconsina; Elpira Asmin; Christiana R. Titaley (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
One of the factors that can lead to an increase in COVID-19 cases is the lack of public knowledge about how to prevent transmission of COVID-19. The increasing number of confirmed cases of COVID-19 requires intervention, not only in terms of implementing health protocols, but also other interventions that are more effective in breaking the chain of transmission of COVID-19, namely vaccination. This study aimed to determine the relationship between public knowledge about COVID-19 and the COVID-19 vaccine and people's attitudes towards the COVID-19 vaccination program in Batu Merah Country. This study applied a cross-sectional design. This study involved 204 samples taken using cluster sampling technique. Data was collected by filling out a questionnaire, then analyzed using the Chi-square test. The results showed that knowledge about COVID-19 was 45% in the low category, knowledge about the COVID-19 vaccine was 59% in the fairly high category, and people's attitudes towards the COVID-19 vaccination program were 55.4% in the agree category. The results of the Chi-square test showed a value of p = 0.0001. Furthermore, it was concluded that there was a relationship between knowledge about COVID-19 and the COVID-19 vaccine and people's attitudes towards the COVID-19 vaccination program in Negeri Batu Merah, Maluku.Keywords: COVID-19; vaccination; knowledge; attitude ABSTRAK Salah satu faktor yang dapat mengakibatkan peningkatan kasus COVID-19 adalah kurangnya pengetahuan masyarakat tentang cara mencegah penularan COVID-19. Jumlah kasus terkonfirmasi COVID-19 yang terus meningkat perlu diintervensi, tidak hanya dari sisi penerapan protokol kesehatan, namun juga intervensi lain yang lebih efektif untuk memutus mata rantai penyebaran COVID-19, yaitu vaksinasi. Penelitian ini bertujuan untuk mengetahui hubungan antara pengetahuan masyarakat tentang COVID-19 dan vaksin COVID-19 dengan sikap masyarakat terhadap program vaksinasi COVID-19 di Negeri Batu Merah. Penelitian ini menerapkan rancangan cross-sectional. Penelitian ini melibatkan 204 sampel yang diambil menggunakan teknik cluster sampling. Data dikumpulkan melalui pengisian kuesioner, lau dianalisis menggunakan uji Chi-square. Hasil penelitian menunjukkan bahwa pengetahuan tentang COVID-19 adalah 45% dalam kategori rendah, pengetahuan tentang vaksin COVID-19 adalah 59% dalam kategori cukup tinggi, dan sikap masyarakat terhadap program vaksinasi COVID-19 adalah 55,4% dalam kategori setuju. Hasil uji Chi-square menunjukkan nilai p = 0,0001. Selanjutnya disimpulkan bahwa ada hubungan antara pengetahuan tentang COVID-19 dan vaksin COVID-19 dengan sikap masyarakat terhadap program vaksinasi COVID-19 di Negeri Batu Merah, Maluku.Kata kunci: COVID-19; vaksinasi; pengetahuan; sikap